An analysis of Said nursi’s contributions to the revitalization of Islamic spirituality in the modern era - Ali Aydogan,; Ahmad Fakhrurrazi Mohammed Zabidi,; Mohd Al Adib Samuri, (Penerbit Universiti Kebangsaan Malaysia, 2025)
For a long time in human history, Islamic civilization and spirituality have always stood out for their dynamism and has been able to adapt to the challenges of every era. In this modern era, Said Nursi emerged as an important figure in the revival of Islamic spirituality. The main purpose of this study is to analyze Said Nursi’s contributions to the revival of Islamic spirituality in the modern era by focusing on the concept of faith in the face of materialist thought and secularization, which emerged in the West and had negative effects on the world and Muslim societies. To carry out this study, a qualitative approach through content analysis was utilized, specifically qualitative content analysis to examine the textual material. The findings in this article illustrate Nursi’s analysis of the problems faced by the Islamic world in the modern era and the reasons for its physical and spiritual defeat by non-Muslims. This study discusses and analyzes Nursi’s proposed solutions to these problems.